Graded recruitment of pupil-linked neuromodulation by parametric stimulation of the vagus nerve - Zakir Mridha (Nature Portfolio, 2021)
Despite its wide and growing use, the mechanisms by which in vivo vagus nerve stimulation (VNS) exerts its therapeutic benefits are still largely unknown. Here, the authors show in mice that pupil dilation is a reliable and noninvasive biosensor for titratable VNS-evoked cortical neuromodulation by acetylcholine.